PEMIKIRAN EKONOMI BAPAK EKONOMI ISLAM; IBNU KHALDUN - Huda, Choirul (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
Economic issues discussed by Ibn Khaldun in his book that in section V. Economic motive arises because human desires are unlimited, being goods that will satisfy his needs were very limited. Therefore, to solve the economic problems must be viewed from two angles; corner power ( werk, arbeid ) and from the point of use. Ibn Khaldun also talks about personal business and general busines. It was described on the explanation of the terms 1 ( maasy and Rizqy ) and the terms 2 ( tamawwul and kasab ). On currencies, Ibn Khaldun predicts that both will be taking place in the world s most important economy , namely: first, becoming exchanger and price measures, as the value of the business (makasib); secondly, a means of transportation, such as deviezen (qaniah); and third, an instrument deposits in banks (zakhirah). In addition to the things already mentioned above, there are still some other things discussed Ibn Khaldun relation to the economys problems. But the bottom line is, Ibn Khaldun through his work does not already represent the most Muslim scientists in the world arena of economic thought. In fact, not in order to praise it exceeds the limit, at least he has contributed to the European renaissance.